2012
DOI: 10.1038/mi.2011.47
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary CD103+ dendritic cells prime Th2 responses to inhaled allergens

Abstract: Allergic asthma stems largely from the actions of T helper 2 (Th2) cells, but the pathways that initiate Th2 responses to inhaled allergens are not fully understood. In the lung, there are two major subsets of dendritic cells (DCs), displaying CD11b or CD103. We found that after taking up inhaled ovalbumin in vivo, purified CD103+ DCs from the lung or lung-draining lymph nodes primed Th2 differentiation ex vivo. Th2 induction by CD103+ DCs was also seen when cockroach or house dust mite allergens were used. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
151
4
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(169 citation statements)
references
References 55 publications
10
151
4
4
Order By: Relevance
“…There has been some debate about which DC subset in the lung contributes to this process. Using ex vivo isolated DCs from the lungs of D. pteronyssinus-challenged mice, Nakano et al (29) showed that CD103 + DCs selectively primed Th2 cells, whereas CD11b + DCs were responsible for Th1 skewing. They substantiated this claim by showing that BXH2 mice, which possess a point mutation in the IRF8 coding region and lack CD103 + DCs, fail to mount a robust Th2 response after D. pteronyssinus treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been some debate about which DC subset in the lung contributes to this process. Using ex vivo isolated DCs from the lungs of D. pteronyssinus-challenged mice, Nakano et al (29) showed that CD103 + DCs selectively primed Th2 cells, whereas CD11b + DCs were responsible for Th1 skewing. They substantiated this claim by showing that BXH2 mice, which possess a point mutation in the IRF8 coding region and lack CD103 + DCs, fail to mount a robust Th2 response after D. pteronyssinus treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, these cells mainly act at the late stage of inflammation by secreting chemokine and presenting Ag within the lung tissue (27). The exact contribution of each lung-resident DC subset to the pathogenesis of dust mite allergy is not conclusive, as studies using ex vivo sorted lung DCs have led to conflicting reports about the contribution of CD103 + and CD11b + DCs to Th2 priming (27)(28)(29). In addition, although mouse models that permit the selective depletion of lung CD103 + DCs exist (30,31), it has only recently been possible to specifically deplete resident lung CD11b + DCs.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…1 DCs, which comprise another lung DC subset, are closely associated with airway epithelium and can prime Th2 differentiation (34). Lower numbers of CD103…”
Section: Discussionmentioning
confidence: 99%
“…3 By contrast, Nakano et al 4 found that CD11b þ CD103 À cells preferentially drive Th1 and CD11b À CD103…”
Section: Introductionmentioning
confidence: 99%